Thiazole Containing Heterocycles with Antimalarial Activity - Kumawat, Mukesh K. (Current Drug Discovery Technologies, 2018)
Background: Heterocyclic compounds are the main class of medicinally important compounds. Many heterocyclic compounds bearing a five-membered ring in their structure have a good spectrum of biological activities. Thiazole is an important class of five-membered heterocyclic compounds. Thiazole and its derivatives exhibited a broad range of biological activities due to the presence of various reaction posseses. Thiazole, heterocyclic nucleus is present in several potent pharmacologically active molecules such as Sulfathiazole (antimicrobial drug), Ritonavir (antiretroviral drug), Tiazofurin (antineoplastic drug) and Abafungin (antifungal drug) etc. The search for some novel biologically active thiazoles is to be continued in the field of medicinal chemistry for investigators. An aim of this review is to identify and try making a SAR (Structure Activity Relationship) of substituted thiazole nucleus as possible new antimalarials. Method: Author undertook a structured search of bibliographic databases for peerreviewed research literature using a focused review question and inclusion/exclusion criteria. The quality of retrieved papers was appraised using standard tools. The characteristics of screened papers were described, and a deductive qualitative content analysis methodology was applied to analyse the interventions and findings of included studies using a conceptual framework. Result: Fifteen papers were included in the review; the majority were described about many biological activity of thiazole nucleus. Seven papers were find that had impacted upon the thaizoles as antimalarials. Some papers focused on the design, synthesis and antimalarial activity evaluation of thiazole derivatives. This review identified and made a SAR (Structure Activity Relationship) of substituted thiazole nucleus as possible new antimalarials. Conclusion: This review describes ongoing research in the search for novel thiazoles as targets and new antimalarial drug molecules.
Keywords: Malaria